Measures of Work-life Balance and Interventions of Reasonable Accommodations for the Return to Work of Cancer Survivors: A Scoping Review - Giuliana Buresti; Bruna Maria Rondinone; Antonio Valenti; Fabio Boccuni; Grazia Fortuna; Sergio Iavicoli; Maria Cristina Dentici; Benedetta Persechino (Elsevier, 2024)
Background: Nearly half of patients diagnosed with cancer are in the middle of their traditional working age. The return to work after cancer entails challenges because of the cancer or treatments and associated with the workplace. The study aimed at providing more insight into the occupational outcomes encountered by workers with cancer and to provide interventions, programs, and practices to support their return to work. Methods: A scoping review was conducted using the Arksey and O'Malley framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for scoping review guidelines. Relevant studies were systematically searched in PubMed/MEDLINE, SCOPUS and Grey literature from 01 January 2000 to 22 February 2024. Results: The literature search generated 3,017 articles; 53 studies were considered eligible for this review. Most of the studies were longitudinal and conducted in Europe. Three macroarea were identified: studies on the impact of cancer on workers in terms of sick leave, employment, return to work, etc.; studies reporting wider issues that may affect workers, such as the compatibility of treatment and work and employment; studies reporting interventions or policies aiming to promote the return to work. Conclusion: There is a lack in the literature in defining multidisciplinary interventions combining physical, psycho-behavioural, educational, and vocational components that could increase the return-to-work rates. Future studies should focus on interdisciplinary return to work efforts with multiple stakeholders with the involvement of an interdisciplinary teamwork (healthcare workers and employers) to combine these multidisciplinary interventions at the beginning of sick leave period.